Analisis Hukum Status Pergantian Jenis Kelamin Berdasarkan Penetapan Ma Nomor 517/Pdt.P/2012/PN YK - Made Utari Purwaningrum; Diangsa Wagian (Fakultas Hukum Universitas Mataram, 2022)
This study aims to determine the basis for judges' considerations in adjudicating and deciding gender change cases in the Yogyakarta District Court. This research uses normative research. The purpose and benefit of this research is to find out what is the basis for the judge's consideration in deciding and adjudicating this gender change case in the Yogyakarta District Court and its legal consequences after the judgment of compensation was handed down by the judge. The results of this study are the judges' considerations in deciding the applicant's petition, namely transgender perpetrators are assessed in terms of the background of the applicant's actions for sex change, the applicant's physical and psychological condition as well as witness testimony from the applicant's closest person. person, namely transgender perpetrators and the legal consequences of the recording. civil applicants related to Law Number 24 of 2013 concerning Population Administration.